Concepts of Learning and Instruction from the Perspective of Learning Theories and Islamic Education - Hartinawanti H; Basri B; Yuspiani Y; M. Shabir U (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Learning and instruction are two main concepts in the field of education that are interconnected yet have different characteristics. This article aims to analyze the influence of behaviorism, cognitivism, and constructivism theories on instructional design, explain the difference between learning as an individual activity and instruction as a social interaction from the perspective of Islamic education, and examine the role of intrinsic and extrinsic motivation in the effectiveness of project-based learning. This study uses a library research approach by analyzing various relevant scientific sources. The study results show that behaviorism emphasizes changes in behavior through stimulus and response, cognitivism focuses on mental processes in learning, while constructivism places learners as active subjects in constructing knowledge. In Islamic education, learning is seen as an individual activity that has the value of worship, whereas teaching is a social process that is filled with the values of exemplary conduct and educational interaction. In addition, intrinsic motivation has been proven to be more dominant in enhancing the effectiveness of project-based learning compared to extrinsic motivation. Therefore, the integration of modern learning theories with the values of Islamic education becomes important to create learning that is meaningful, humanistic, and relevant to the needs of the 21st century.